Human TUBB3 Mutations Disrupt Netrin Attractive Signaling. (15th March 2018) - Huang, Huai; Yang, Tao; Shao, Qiangqiang; Majumder, Tanushree; Mell, Kristopher; Liu, Guofa
Highlights: TUBB3 mutations impair the interaction of DCC with TUBB3. TUBB3 mutations perturb netrin-1-induced interaction of DCC with polymerized TUBB3 in MTs. TUBB3 mutations block netrin-1-induced neurite outgrowth and branching. TUBB3 mutations inhibit netrin-1-promoted commissural axon attraction. TUBB3 mutations impair spinal cord commissural axon projection in vivo. Abstract: Heterozygous missense mutations in human TUBB3 gene result in a spectrum of brain malformations associated with defects in axon guidance, neuronal migration and differentiation. However, the molecular mechanisms underlying mutation-related axon guidance abnormalities are unclear. Recent studies have shown that netrin-1, a canonical guidance cue, induced the interaction of TUBB3 with the netrin receptor deleted in colorectal cancer (DCC). Furthermore, TUBB3 is required for netrin-1-induced axon outgrowth, branching and pathfinding. Here, we provide evidence that TUBB3 mutations impair netrin/DCC signaling in the developing nervous system. The interaction of DCC with most TUBB3 mutants (eight out of twelve) is significantly reduced compared to the wild-type TUBB3. TUBB3 mutants R262C and A302V exhibit decreased subcellular colocalization with DCC in the growth cones of primary neurons. Netrin-1 increases the interaction of endogenous DCC with wild-type human TUBB3, but not R262C or A302V, in primary neurons. Netrin-1 also increases co-sedimentation of DCC with polymerized microtubules (MTs) in primary neurons expressing the wild-type TUBB3, but not R262C or A302V. Expression of either R262C or A302V not only suppresses netrin-1-induced neurite outgrowth, branching and attraction in vitro, but also causes defects in spinal cord commissural axon (CA) projection and pathfinding in ovo . Our study reveals that missense TUBB3 mutations specifically disrupt netrin/DCC-mediated attractive signaling.